(3bQYI GdWjhQs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdWGhS L W SDGdc Yf bVGA GdMGLI dYed Edi YOO GdbQYI, SDGdc Yf GdJMhjd hGdfbd CSQY JfGd cdeG JQjOs
(3BNQgG (B:s
(3BNQgG(B: (3SDGdc Yf GdMX ef GdSdWGf JfGd efg GdLGg hGdYR, SDGdc GdhUhd Edi GdeQGe GWeY aEfg jMUd dc , SDGdc Yf GdTQcI GMPQ dG JTGQc djS ajg NjQs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs